Labour markets in a Post-Keynesian growth model: The effects of endogenous productivity growth and working time reduction - Stefan Ederer; Armon Rezai (Austrian Institute of Economic Research (WIFO), 2020)
We study endogenous employment and distribution dynamics in a Post-Keynesian model of Kalecki-Steindl tradition. Productivity adjustments stabilise employment and the labour share in the long run: technological change allows firms to replenish the reserve army of workers in struggle over income shares and thereby keep wage demands in check. We discuss stability conditions and the equilibrium dynamics. This allows us to study how legal working time and its reduction affect the equilibrium. We find that a demand shock is likely to lower the profit share and increase the employment rate. A supply shock in contrast tends to have detrimental effects on employment and income distribution. Labour market institutions and a working time reduction have no long-term effect on growth, distribution and inflation in the model. The effects on the level of capital stock and output however are positive in a wage-led demand regime. Furthermore, an erosion of labour market institutions dampens inflation temporarily. The model provides possible explanations as to the causes of several current economic phenomena such as secular stagnation, digitalisation, and the break-down of the Philips curve.
Keywords: D33; E12; E24; O40; 330; Post-Keynesian economics; productivity; technological change; incomedistribution; employment